Thyroid hormone response element organization dictates the composition of active receptor - Velasco, Lara Franciele Ribeiro (2007)
Thyroid hormone (triiodothyronine, T3) is known to activate transcription by binding heterodimers of thyroid hormone receptors (TRs) and retinoid X receptors (RXRs). RXR-TRs bind to T3 response elements (TREs) composed of direct repeats of the sequence AGGTCA spaced by four nucleotides (DR-4). In other TREs, however, the half-sites can be arranged as inverted palindromes and palindromes (Pal). Here we show that TR homodimers and monomers activate transcription from representative TREs with alternate half-site placements. TRβ activates transcription more efficiently than TRα at an inverted palindrome (F2), and this correlates with preferential TRβ homodimer formation at F2 in vitro. Furthermore, reconstruction of TR transcription complexes in yeast indicates that TRβ homodimers are active at F2, whereas RXR-TRs are active at DR-4 and Pal. Finally, analysis of TRβ mutations that block homodimer and/or heterodimer formation reveal TRE-selective requirements for these surfaces in mammalian cells, which suggest that TRβ homodimers are active at F2, RXR-TRs at DR-4, and TR monomers at Pal. TRβ requires higher levels of hormone for activation at F2 than other TREs, and this differential effect is abolished by a dimer surface mutation suggesting that it is related to composition of the TR·TRE complex. We propose that interactions of particular TR oligomers with different elements play unappreciated roles in TRE-selective actions of liganded TRs in vivo.